Genes associated with MUC5AC expression in small airway epithelium of human smokers and non-smokers - Wang Guoqing; Xu Zhibo; Wang Rui; Al-Hijji Mohammed; Salit Jacqueline; Strulovici-Barel Yael; Tilley Ann E; Mezey Jason G; Crystal Ronald G (BMC, 2012)
Abstract Background Mucus hypersecretion contributes to the morbidity and mortality of smoking-related lung diseases, especially chronic obstructive pulmonary disease (COPD), which starts in the small airways. Despite progress in animal studies, the genes and their expression pattern involved in mucus production and secretion in human airway epithelium are not well understood. We hypothesized that comparison of the transcriptomes of the small airway epithelium of individuals that express high vs low levels of MUC5AC, the major macromolecular component of airway mucus, could be used as a probe to identify the genes related to human small airway mucus production/secretion. Methods Flexible bronchoscopy and brushing were used to obtain small airway epithelium (10th to 12th order bronchi) from healthy nonsmokers (n=60) and healthy smokers (n=72). Affymetrix HG-U133 plus 2.0 microarrays were used to assess gene expression. Massive parallel sequencing (RNA-Seq) was used to verify gene expression of small airway epithelium from 5 nonsmokers and 6 smokers. Results MUC5AC expression varied 31-fold among the healthy nonsmokers. Genome-wide comparison between healthy nonsmokers (n = 60) grouped as "high MUC5AC expressors" vs "low MUC5AC expressors" identified 528 genes significantly up-regulated and 15 genes significantly down-regulated in the high vs low expressors. This strategy identified both mucus production and secretion related genes under control of a network composed of multiple transcription factors. Based on the literature, genes in the up-regulated list were used to identify a 73 "MUC5AC-associated core gene" list with 9 categories: mucus component; mucus-producing cell differentiation-related transcription factor; mucus-producing cell differentiation-related pathway or mediator; post-translational modification of mucin; vesicle transport; endoplasmic reticulum stress-related; secretory granule-associated; mucus secretion-related regulator and mucus hypersecretory-related ion channel. As a validation cohort, we assessed the MUC5AC-associated core gene list in the small airway epithelium of an independent set of healthy smokers (n = 72). There was up-regulation of MUC5AC in the small airway epithelium of smokers (2.3-fold, p < 10-8) associated with a coordinated up-regulation of MUC5AC-associated core gene expression pattern in the small airway epithelium of smokers (p < 0.01). Deep sequencing confirmed these observations. Conclusion The identification of the genes associated with increased airway mucin production in humans should be useful in understanding the pathogenesis of airway mucus hypersecretion and identifying therapeutic targets. Author summary Mucus hypersecretion contributes to the morbidity and mortality of smoking-related lung diseases, especially chronic obstructive pulmonary disease (COPD), which starts in the small airways. Little is known about the gene networks associated with the synthesis and secretion of mucins in the human small airway epithelium. Taking advantage of the knowledge that MUC5AC is a major mucin secreted by the small airway epithelium, the expression of MUC5AC in small airway epithelium is highly regulated at the transcriptional level and our observation that healthy nonsmokers have variable numbers of MUC5AC+ secretory cells in the human small airway epithelium, we compared genome-wide gene expression of the small airway epithelium of high vs low MUC5AC expressors from 60 nonsmokers to identify the genes associated with MUC5AC expression. This novel strategy enabled identification of a 73 "MUC5AC-associated core gene" list with 9 categories, which control a series of processes from mucin biosynthesis to mucus secretion. The coordinated gene expression pattern of MUC5AC-associated core genes were corroborated in an independent cohort of 72 healthy smokers. Deep sequencing of small airway epithelium RNA confirmed these observations. This finding will be useful in identifying therapeutic targets to treat small airway mucus hypersecretion.